Knowledge, Attitudes, and Practices on Oral Health of Children Living in Alternative Care (CLIAC) Ages 6-12 Years Old: A Basis for Dental Health Program - Imperio, Kevin Brendt P.; De Leon, Chelsea Fiel J.; Fajilan, Kristine Love G.; Valenzuela, Ria Anne A.; Subido, Nathalya Bmay A.; Perez, Roderick C.; Taclan, Lorcelie B.; Mergal, Vicky C. (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
Oral diseases continue to be a serious public health problem in the Philippines, especially Children Living in Alternative Care (CLIAC). This study aims to determine the knowledge, attitudes, and practices on Oral Health of CLIAC ages 6-12 years old as a basis for a dental health program. A descriptive quantitative study was conducted at an institution in Batangas among 38 respondents. Questionnaires were used to collect data which were encoded in SPSS software to generate the mean scores for each of the given questions and their standard deviation. The study found that the CLIAC has high knowledge of oral health but showed poor results on replacing toothbrushes and tooth brushing pressure. The CLIAC had a neutral attitude on oral health but showed a negative attitude towards the taste of the toothpaste, perspective towards the dentist, and the effects of nutrition and diet on oral health. The CLIAC has a fair practice towards oral health as evidenced by their good practice in performing oral hygiene, nutrition, and diet; fair practices on mouthwash, dental visits, sweet and soft drinks consumption; and poor practices on flossing. A dental health program was developed based on the results of this study for these CLIAC. The aim of the program was to maintain and enrich knowledge, enhance attitude, and improve practices on oral health. It is recommended that the same program should be tested for its effectiveness in increasing the CLIAC’s knowledge, attitude, and practices towards their oral health. Keywords : public health, dental health program, children living in alternative care, alternative care, oral health